Regional blockade in endoscopic surgical removal of pituitary adenoma - N Akhmadov; E Nasibova (Медицина болю)
Backround. The endoscopic endonasal transsphenoidal approach is gaining popularity as an alternative to the traditional technique for removing pituitary adenomas using an operating microscope. In transnasal transsphenoidal resection of pituitary tumors, bilateral regional anesthesia of the pterygopalatine fossa, performed through subzygomatic access, has been found to be the most optimal technique.